THE 2005 PARLIAMENTARY ELECTIONS IN AZERBAIJAN: INFLUENCING FACTORS1 - NURIEV, Elkhan (CENTRAL ASIA AND THE CAUCASUS, 2006)
Two years after he was elected head of state, Ilkham Aliev was confronted with the threat of a possible political crisis in Azerbaijan. On 6 November 2005, the country went to the polls to elect the parliament. According to the opposition leaders, the process abounded in serious violations and massive falsifications of the election results. The ruling elite, however, insists that the country had all the conditions for a fair, transparent, and democratic election campaign. From the very beginning, international organizations spared no effort to make the elections a fair process. At the very beginning of the election campaign, the United States, the key actor in the region, sent contradictory signals about its possible response if falsifications were revealed and recognized. It should be said that the current political processes in the republic began in 2003, after the death of President Heydar Aliev, who kept the country under strict control. After Ilkham Aliev, his son, was elected president of the country, he found himself completely dependent on the “old guard.” Decentralization of the state’s political structure began; the political situation became very complicated: some of the cabinet members entered into an open confrontation with others and created influential groups for this purpose. Chairman of the State Customs Committee Kemalladin Heydarov and Minister of Economic Development Farkhad Aliev were locked in a struggle for influence on the president and his closest circle. Bitter rivalry among different groups inside the ruling elite has always been a prominent feature of the country’s political life, even though many foreign observers were inclined to describe the situation as a confrontation between power and opposition. On the eve of the presidential election, the leading opposition parties, which stepped up their activity, added to the tension created by the growing contradictions between the key cabinet members. The opposition leaders threatened a Color Revolution if the ruling elite failed to organize fair elections. The country’s leaders responded to these radical statements with harsh measures and resolutely stemmed the opposition’s attempts to rally people in anti-government actions, including demonstrations in the center of Baku. At the same time, some of the top bureaucrats, while demonstrating their loyalty to the president and the ruling party, were maintaining unofficial contacts with the opposition. Shortly before the election, they stopped pretending and revealed their bias toward the opposition leaders and their cause. In fact, several weeks before the election, Azeri society was living in anticipation of an orange revolution. The law enforcement bodies took every measure to prevent destabilization; the opposition leaders were absolutely convinced that a revolution offered the only possibility of changing the regime and coming to power. The current events can be described as an ongoing political struggle between the ruling Novy Azerbaijan (New Azerbaijan) Party, the opposition bloc Svoboda (Freedom), and other forces. In other words, the parliamentary election became an episode in a bitter power struggle, the first round of which went to the president. Several weeks before the election, Ilkham Aliev surprised everybody by making several political moves to forestall an attempt at a coup d’état. Still, political tension remained.